Evaluation of self-healing epoxy coatings for steel reinforcement. (10th December 2018) - Weishaar, Adrienne; Carpenter, Matthew; Loucks, Ryan; Sakulich, Aaron; Peterson, Amy M.
Highlights: Rebar with self-healing coatings outperforms controls in corrosion testing. Self-healing coatings on rebar outperform in all damage cases. Self-healing coatings on steel coupons were less consistent. Addition of microcapsules did not significantly affect coating adhesion after 28 days of testing according to ASTMD3359 . Abstract: Epoxy coatings are currently the most popular corrosion protection mechanism for steel reinforcement in structural concrete in North America. However, these coatings are easily damaged on worksites, negating their intended purpose. This study investigated self-healing coatings for steel reinforcement to introduce an autonomous healing mechanism for damaged coatings. Coatings were applied to steel coupons and rebar, intentionally damaged, and introduced to a corrosive environment via salt-water aeration tanks and accelerated corrosion testing. Performance of the experimental coatings was evaluated qualitatively and quantitatively. Adhesion strength and effects of coating thickness were also studied. Results from pre-corroded coated steel coupons submerged in salt-water aeration tanks exhibited improved corrosion resistance performance with self-healing coatings, although self-healing and conventional coatings performed similarly under other conditions. Steel reinforcement with a self-healing coating embedded in concrete and subjected to accelerated corrosion testing lasted longer than the conventionally coated counterparts. Self-healing coatings had comparable adhesion to the substrate as do conventional coatings. With numerous avenues for future research towards the adoption of self-healing coatings for steel reinforcement, this paper shows preliminary results demonstrating the potential benefits of their use.